Identification and characterization of L-lysine decarboxylase from Huperzia serrata and its role in the metabolic pathway of lycopodium alkaloid. (April 2017) - Xu, Baofu; Lei, Lei; Zhu, Xiaocen; Zhou, Yiqing; Xiao, Youli
Abstract: Lysine decarboxylation is the first biosynthetic step of Huperzine A (HupA). Six cDNAs encoding lysine decarboxylases (LDCs) were cloned from Huperzia serrata by degenerate PCR and rapid amplification of cDNA ends (RACE). One HsLDC isoform was functionally characterized as lysine decarboxylase. The HsLDC exhibited greatest catalytic efficiency ( k cat / K m, 2.11 s −1  mM −1 ) toward L-lysine in vitro among all reported plant-LDCs. Moreover, transient expression of the HsLDC in tobacco leaves specifically increased cadaverine content from zero to 0.75 mg per gram of dry mass. Additionally, a convenient and reliable method used to detect the two catalytic products was developed. With the novel method, the enzymatic products of HsLDC and HsCAO, namely cadaverine and 5-aminopentanal, respectively, were detected simultaneously both in assay with purified enzymes and in transgenic tobacco leaves. This work not only provides direct evidence of the first two-step in biosynthetic pathway of HupA in Huperzia serrata and paves the way for further elucidation of the pathway, but also enables engineering heterologous production of HupA. Graphical abstract: Biofunctional characterization of HsLDCs from H. serrata and simultaneous detection of enzymatic products of HsLDC and HsCAO in both in vitro and in vivo assays. Highlights: Six cDNAs encoding HsLDCs were isolated from Huperzia serrata. HsLDC-X1 showed preference for L-lysine in vivo. HsLDC-X1 showed similar catalytic efficiencies to L-lysine and L-ornithine in vitro. Enzymatic products were simultaneously detected by a convenient method. 5-Aminopentanal can be produced by HsLDC-CAO coupled assays in vitro and in vivo.